1967
DOI: 10.1139/y67-028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Quaternary Bases and Inorganic Cations on Acetylcholine Synthesis in Nervous Tissue

Abstract: A number of quaternary bases were tested for their ability to inhibit the synthesis of acetylcholine (ACh) by incubated minced mouse brain. Tetramethyl-, tetraethyl-, tetrapropyl-, and tetrabutyl-ammonium were moderately active as inhibitors, the strongest being the tetraethyl base (TEA), which was 1–2% as active as the hemicholinium HC-3. Weaker activity was exhibited by hexamethonium, d-tubocurarine, and tolazoline; NH4Cl and N-methylnicotinamide were inactive at concentrations up to 10−2 M. Except in high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1968
1968
1991
1991

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…This explanation is supported by the results that the synthesis was also augmented by circumferential distension when eserine was omitted from the medium and disappeared again by adding 1 x 10-8 g/ml or more ACh to the medium, and that the pre-incubated pre parations which contained a considerable amount of free ACh in the tissue failed to in crease the amount of bound ACh even when the longitudinal distension was applied. Con trol of ACh synthesis by released ACh itself in the nerve endings has been reported by Bhat nagar and Maclntosh (22) and Szerb and Somogyi (23). Potter (24) has also demonstrated that ACh is a weak competitive inhibitor of choline uptake in the presence of eserine.…”
Section: Degree Of Distension and Free Achmentioning
confidence: 67%
“…This explanation is supported by the results that the synthesis was also augmented by circumferential distension when eserine was omitted from the medium and disappeared again by adding 1 x 10-8 g/ml or more ACh to the medium, and that the pre-incubated pre parations which contained a considerable amount of free ACh in the tissue failed to in crease the amount of bound ACh even when the longitudinal distension was applied. Con trol of ACh synthesis by released ACh itself in the nerve endings has been reported by Bhat nagar and Maclntosh (22) and Szerb and Somogyi (23). Potter (24) has also demonstrated that ACh is a weak competitive inhibitor of choline uptake in the presence of eserine.…”
Section: Degree Of Distension and Free Achmentioning
confidence: 67%
“…This was not done in the present experiments. Bhatnagar & MacIntosh (1967) pointed out that the inhibition of ACh synthesis obtained by Mann et al with excessively high KCl concentrations may have been the result of the removal of the Na from the medium, and they produced evidence in favour of this view.…”
Section: Discussionmentioning
confidence: 98%
“…A regulating negative feed-back mechanism between the ACh concentration in the tissue and the rate of ACh formation has been postulated by Mann et al (1939) on the basis of the stimulating effect of potassium, but a second negative feed-back mechanism may exist between the ACh concentration in the environment of a store of ACh and the rate of its release. In favour of such a mechanism are the recent findings that the release of ACh from minced brain (Bhatnagar & MacIntosh, 1967) and from the synaptosome fraction of a brain homogenate (Hosein, Levy & Ko, 1967) is inhibited by the addition of ACh to the medium. If ACh receptors were involved in this negative feed-back system, their sensitivity might be reduced by atropine.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous experience with (-)-vesamicol, we have now used this compound along with troxypyrrolium, an inhibitor of the nerve terminal highaffinity sodium-dependent choline uptake system (Bhatnagar & MacIntosh, 1967), to determine whether transmitter release at the rat NMJ could, as in the snake, be demonstrated to be heterogeneous. Other workers who have investigated the effects of vesamicol on transmitter release at frog (Van der Kloot, 1986;Enomoto, 1988;Lupa, 1988) and mouse (Whitton, Marshall & Parsons, 1986) NMJs have found no evidence for the heterogeneous release of more than one population of quanta.…”
Section: Introductionmentioning
confidence: 99%